Lessons from Hedge Fund Fraud - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2009)
We examine two of the most fascinating fraud cases that rocked the hedge fund industry: Bernard L. Madoff Investment Securities and Bayou Management. From academic research and news reports, we distill important lessons for the hedge fund investor. Our key conclusions are (i) conflicts of interests are often symptomatic of more serious problems at hedge funds, (ii) auditing statements from obscure accounting firms should provide little assurance to investors, (iii) a comparison between the actual fund risk exposures based on realized returns with the theoretical risk exposures from the trading strategy serves as a useful cross-check for investors, and (iv) for funds with a master-feeder structure, it is important to conduct due diligence on both the master and the feeder fund.